Socio-ecological determinants of older people’s mental health and well-being during COVID-19: A qualitative analysis within the Irish context - Guzman, Viveka; Doyle, Frank; Foley, Ronan; Craven, Peter; Crowe, Noelene; Wilson, Penny; Smith, Ailbhe; Hegarty, Gerry; Pertl, Maria M. (Frontiers in Public Health, 2023)
Evidence indicates that older people with biological and social vulnerabilities are at high risk of short- and long-term consequences related to the COVID-19 pandemic. However, studies have also highlighted that the crisis may present opportunities for personal growth if older individuals are met with appropriate resources and support. The aim of this study was to explore the perceptions of older people regarding how individual, social, and environmental factors have supported or hindered their well-being and health during COVID-19. We analyzed data collected between April-May and October-November 2021 from the Well-being, Interventions and Support during Epidemics (WISE) study, a qualitative investigation of community-dwellers based in Ireland and aged 65 years or over. Participants (n=57) completed written submissions, narrative interviews and/or go-along interviews detailing their experiences during the pandemic. Framework analysis was carried out in NVivo 12 to identify determinants, linkages, and explanations within Bronfenbrenner’s socio-ecological model. The mean age of participants was 74.9 years, 53% were female, 45% lived alone, and 86% lived in areas with high urban influence. Our findings highlight the heterogeneous effect of COVID-19 across diverse older individuals who held distinct concerns, capabilities, and roles in society before and during the pandemic. Multi-scalar contextual characteristics such as individual’s living arrangements, neighborhood social and built environments, and social expectations about aging and help-seeking, had an influential role in participants’ well-being and available supports. We identified mixed views regarding public health restrictions, but a consensus emerged questioning the suitability of one-size-fits-all approaches based on chronological age. Our results suggest that some negative consequences could have been avoided by increasing collaboration with older people and with the provision of clearer communications. The interdependencies identified between individual characteristics and socio-ecological factors that influenced participants’ availability of supports and development of adaptive strategies represent areas of opportunity for the development of age-friendly interventions during and beyond public health crises.